Actions of procaine on specific nociceptive cells in leech central nervous system - Johansen, J (J Neurosci, 1984)
The effects of the local anesthetic, procaine, on the electrophysiological properties of the leech neurons responding to nociceptive stimuli (N cells) were examined in isolated segmental ganglia in Macrobdella . In the N cell situated laterally in ganglia 7 to 19, procaine produced a depolarization; whereas in the N cell situated medially, it caused a hyperpolarization. These changes in membrane potential were accompanied by a decrease in input resistance, persisted in solutions containing 20 mM MgCl2, and were reversible after drug washout. The depolarization induced by procaine in the lateral N cell was abolished in Na-free solutions. The hyperpolarization produced by procaine in the medial N cell persisted in low chloride solutions and was enhanced by about 30% when the K concentration was reduced to one-tenth of its control value. Therefore, it seems likely that an increase in the resting K conductance was a contributing factor to this hyperpolarization. Procaine greatly prolonged the action potential of the lateral but not the medial N cell. This effect was not solely a consequence of the membrane potential change produced by the drug. Ganglia 5, 6, 20, and 21 contained two rather than four cells with N-like properties. These neurons were N-like by virtue of the shape of their action potential and their morphological similarities to the N cells found in ganglia 7 to 19, as well as by their selective sensitivities to nociceptive mechanical stimulation of the skin. The cells in ganglia 5 and 6 responded to gut stimulation, as did the medial N cells in ganglia 7 to 19.(ABSTRACT TRUNCATED AT 250 WORDS)